Morphology and composition of drumlins in the forefield of Nordenskiöldbreen, central Spitsbergen - Nína Aradóttir 1990- (2015)
Drumlins are important glaciogenic landforms that can be useful to reconstruct earlier glaciations. Their morphology and composition can be highly variable and their formation is still not fully explained. They are among the most studied landforms. Despite that drumlins have not been described on land in Svalbard. The aim of this study is to investigate the morphology and composition of five drumlins in the forefield of Nordenskiöldbreen, Svalbard. The drumlins were formed during the last glacial advance, The Little Ice Age. Based on aerial images and field investigation, it has been concluded that the glacier has retreated approximately 1,5 km on the northern side. The drumlins were exposed in the mid 20th century. They do support earlier theories that the glacier is polythermal and the direction of the former ice flow was ENE to WSW. A TopCon was used to reconstruct their morphology and it does demonstrate how variable the morphology of drumlins can be. Fluvial erosion is considered to be one of the main reasons for that. The drumlins are smaller compared to drumlins in earlier literature. To investigate the composition of the drumlins a section in one of them was logged. It was diveded into two layers based on difference in grain size. They were both interpreted as a till based on clast morpholgy and composition and fabric analysis. Further investigation would be needed for more interpretations about the drumlins. Jökulöldur eru mikilvæg landform í jökulmótuðu landslagi og eru gagnlegar til að endurbyggja fyrri jökulskeið. Form og setgerð þeirra getur verið mjög fjölbreytt og myndun þeirra er enn ekki að fullu útskýrð. Þær eru með mest rannsökuðu landformunum. Þrátt fyrir það hefur jökulöldum á landi ekki verið lýst á Svalbarða. Markmið þessarar rannsóknar var að lýsa formi og setgerð fimm jökulaldna á jökulsvæði Nordenskiöldbreen, Svalbarða. Þær voru myndaðar á síðasta jökulskeiði, Litlu Ísöld. Út frá loftmyndum og rannsóknum í felti hefur verið staðfest að jökullinn hefur hörfað um 1,5 km á norður hlið ...